Um olhar psicanalítico para as consequências psíquicas dos testemunhos do Shoah - Douer, Anna Sverner (2024)
The mandatory undergraduate thesis in question presents an analysis that seeks to understand the psychic consequences of the Shoah (Holocaust) from the perspective of psychoanalysis. Launching a brief historical contextualization of the period of the Nazism, Shoah and psychoanalysis. Then, a specific look for the people of Shoah (survivor/witness) and some consequences arising from this event; impossibility of transmission; trauma; traumatic neurosis; mournings; transgenerational trauma. Finally, the clinical considerations and management